1986
DOI: 10.1111/j.1699-0463.1986.tb02115.x
|View full text |Cite
|
Sign up to set email alerts
|

Revaccination of Adults Against Diphtheria Ii: Combined Diphtheria and Tetanus Revaccination With Different Doses of Diphtheria Toxoid 20 Years After Primary Vaccination

Abstract: Revaccination of adults against diphtheria 11: Combined diphtheria and tetanus revaccination with different doses of diphtheria toxoid 20 years after primary vaccination. Acta path. microbiol. immunol. scand. Sect. C, 94: 219-225, 1986. Immunity following diphtheria vaccination in childhood is temporary, and recent outbreaks of diphtheria in adult populations evoked interest in the effect of and side-reactions to revaccination of adults. 237 military recruits were randomly allocated to revaccination with 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…or s.c.) and method of injection, (3) tetanus antitoxin levels prior to vaccination, (4) the presence (and perhaps quantity) of adjuvants, (5) age of the subjects, and (6) method used to assess reactogenicity (e.g., personal or telephone interviews with or without open or closed questions, diary cards to be filled in by vaccinees, etc.). In any case, the overall incidence of reactions observed (50%) was lower than of that described in some controlled trials (ranging between 70% and 82%) 11,13,14,18 but higher than the incidence reported in another (31%) 15 and somewhat similar to that reported by Middaugh during a mass Td campaign (58%). 17 The reactogenicity profile of Td vaccine observed in this study is consistent with that reported in the literature, 5,11,13,18 except for malaise, which is usually reported less frequently.…”
Section: Discussionsupporting
confidence: 54%
“…or s.c.) and method of injection, (3) tetanus antitoxin levels prior to vaccination, (4) the presence (and perhaps quantity) of adjuvants, (5) age of the subjects, and (6) method used to assess reactogenicity (e.g., personal or telephone interviews with or without open or closed questions, diary cards to be filled in by vaccinees, etc.). In any case, the overall incidence of reactions observed (50%) was lower than of that described in some controlled trials (ranging between 70% and 82%) 11,13,14,18 but higher than the incidence reported in another (31%) 15 and somewhat similar to that reported by Middaugh during a mass Td campaign (58%). 17 The reactogenicity profile of Td vaccine observed in this study is consistent with that reported in the literature, 5,11,13,18 except for malaise, which is usually reported less frequently.…”
Section: Discussionsupporting
confidence: 54%
“…45 However, it has also been observed that the bacteriophage β has the capacity to infect samples of C. diphtheriae, C. pseudotuberculosis and C. ulcerans, thereby constituting a risk of emergence of conditions of diphtheria caused by this species. 1,38,95,99 Variability of the capacity to produce DT, between samples of C. ulcerans, has already been documented. 39,116 The majority of clinical cases in humans and animals have been correlated with DT-producing strains (Tables 1 and 2).…”
Section: Microbiological and Clinical Characteristicsmentioning
confidence: 98%
“…Some samples isolated from patients presenting conditions of extrapharyngeal infection have presented differences in DT sequences, predominantly in the domains of translocation and adherence. 9,70,80,99,109 These facts may contribute towards situations in which individuals vaccinated with diphtheric toxoid or undergoing serum therapy do not present full protection against infections caused by C. ulcerans. Even if it is considered that the diphtheric toxoid may have a protective effect against diphtheria caused by C. ulcerans (i.e.…”
Section: Role Of Diphtheric Toxoid In Preventionmentioning
confidence: 99%
“…22 The increased risk of diphtheria of outbreaks could have been foreseen because immunity after childhood vaccination is temporary. 23 Diphtheria can be treated with diphtheria antitoxin (DAT). However, use of these IgG antibody preparations in developing countries is limited, mainly by high cost.…”
Section: Discussionmentioning
confidence: 99%